KEPEMIMPINAN STRUKTUR ORGANISASI BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA DALAM MANAJEMEN ISLAM - Ade Noviola Fadillah (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Employee performance is an interesting research subject because employee performance is important for organizational sustainability. The purpose of this research is to examine the relationship between organizational structure, work discipline, and employee performance as well as the influence of change management and leadership change on these factors. Other factors examined include the impact of organizational culture and organizational structure on employee performance. The number of employees who became the population of this study were 97 people. The 97 employees who were the sample of the study also represent the general population. Saturated or census sampling techniques are used in the sampling process. This study uses statistical analysis with multiple linear regression techniques and SPSS software. This is a kind of quantitative research. According to the findings of data analysis, change management, innovative leadership, organizational models, organizational culture, work compliance, and change management have a significant impact on employee performance